RELATIONSHIP BETWEEN INTERNAL PRESSURE AND CAVITY VOLUME CHANGE BASED ON LIQUID IMPACT LOADING TO BIMETALLIC THIN-WALLED TUBES - LIU JianWei; SUN ChangYing; LI YuHan; YAO XinQi; FAN XiangWen (Jixie qiangdu)
Liquid Impact Forming（ LIF） of bimetallic thin-walled tubes is a composite forming technology developed on the basis of tube hydroforming and stamping. Internal pressure required for the formation of the bimetallic thin-walled tubes under liquid impact loading is derived from the compression of the volume of the tube blank,and its size varied with the compression of liquid volume. For this purpose,investigation on forming mechanism and variation law of the internal pressure of the bimetallic thin-walled tubes is proposed.Firstly,forming principle of LIF of bimetallic thin-walled tubes was introduced. Secondly,theory of internal pressure was analyzed in the process of the axial impact hydraulic performing and the radial forming of bimetallic thinwalled tubes. Mathematical model between the internal pressure and volume change in the tube blank cavity was obtained.Thirdly,generation regularity of internal pressure of the axial and the radial liquid impact of the bimetallic thin-walled tubes was performed using ANSYS WORKBENCH. Through comparison of numerical simulation and theoretical analysis,it is not difficult to find that they were a good consistency,and the internal pressure model is optimized by the model error revision,which lays a good theoretical and application basis for further research on LIF of bimetallic thin-walled tubes.